2022
DOI: 10.1002/hbm.25825
|View full text |Cite
|
Sign up to set email alerts
|

Increased child‐evoked activation in the precuneus during facial affect recognition in mothers

Abstract: Successful parenting requires constant inferring of affective states. Especially vital is the correct identification of facial affect. Previous studies have shown that infant faces are processed preferentially compared to adult faces both on the behavioural and the neural level. This study specifically investigates the child‐evoked neural responses to affective faces and their modulation by motherhood and attention to affect. To do so, we used a paradigm to measure neural responses during both explicit and imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…This study is the first to compare mothers and non-mothers in a task measuring motivational responses to infant stimuli. Comparing these two groups in a motivationrelated behavioral task provides insight into how previously observed differences in brain activation towards infant stimuli between mothers and non-mothers (e.g., Peltola et al, 2014;Plank et al, 2022;Vuoriainen et al, 2022;Zhang et al, 2020) might also be reflected in behavior. In the future, modifying the paradigms measuring motivational responses to address the factors underlying viewing times in more detail (i.e., whether decreases in looking at crying infant faces are due to willingness to act, aversion to infant crying, or other factors) will be important.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to compare mothers and non-mothers in a task measuring motivational responses to infant stimuli. Comparing these two groups in a motivationrelated behavioral task provides insight into how previously observed differences in brain activation towards infant stimuli between mothers and non-mothers (e.g., Peltola et al, 2014;Plank et al, 2022;Vuoriainen et al, 2022;Zhang et al, 2020) might also be reflected in behavior. In the future, modifying the paradigms measuring motivational responses to address the factors underlying viewing times in more detail (i.e., whether decreases in looking at crying infant faces are due to willingness to act, aversion to infant crying, or other factors) will be important.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, recognizing the emotion of the infant face can facilitate active human interactions. Studies indicated that the recognition of facial expression included several processes, such as processing the visual information and extract relevant features connected to the portrayed information, then infer the affective state based on these features [ 13 ]. Additionally, Kanske et al reported that facial affect recognition combines the affection and cognition of social understanding, which enable such representations via creating vicarious affective states in the observer (empathy) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%